Establishing an Ideologically Aoherent History: Swedish social-democratic historical culture, 1881–1900. Issue 2 (15th March 2017) - Elmersjö, Henrik Åström
Abstract : This article analyses the historical culture of the Swedish Social Democratic Worker's Party (SAP) during its formation in the last decades of the 19th century. Utilizing the theoretical concepts of myth and conceptual metaphor, the sense-making aspects of historical narration are studied, especially the way coherent stories are told, in which the movement under formation is made part of a long history leading to a desirable future. The SAP utilized history both morally-defensively and tactically-offensively. The moral use of history depicts Jesus, Münster, and the French Revolution, establishing the righteousness of revolt. The revolutions of 1848 and the Paris Commune, during which the workers are seen as acting more independently, are depicted in a way that draws attention to tactical aspects; lessons are learned on how the workers should act in a revolutionary situation. As has been shown to be the case regarding national narratives, the sense-making mechanisms of historical narration also tend to appeal to issues of identity. The metaphorical conceptualization of ideas and movements as individuals and families further underlines these issues.